CURRENT TRENDS IN STARTUP FINANCING: OPPORTUNITIES, CHALLENGES, AND EMERGING FUNDING MODELS - Shaymardanova Mohidil Mansurovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Startup companies play a crucial role in driving innovation, economic growth,  and  job  creation  in  the  modern  economy.  However,  access  to  financial resources remains one of the most significant challenges faced by startups, particularly during  the  early  stages  of  development.  In  recent  years,  startup  financing  has undergone  substantial  transformation  due  to  technological  advancements, globalization,  and  the  emergence  of  alternative  funding  mechanisms.  Traditional funding sources such as bank loans and venture capital are increasingly complemented by crowdfunding, angel investment, accelerators, incubators, and government support programs. This theoretical review examines contemporary startup financing models, analyzes  their  advantages  and  limitations,  and  explores  emerging  trends  shaping entrepreneurial ecosystems worldwide. The findings indicate that diversified funding opportunities have improved access to capital for entrepreneurs; however, challenges related to investment risks, market uncertainty, and financial sustainability continue to affect startup growth. The study concludes that successful startup financing requires strategic  planning,  financial  literacy,  and  an  understanding  of  evolving  investment landscapes.